Evolution of Cardiac Damage Staged With Echocardiography in Fabry Disease - Rosa Lillo; Maria Chiara Meucci; Annamaria Del Franco; Emanuele Monda; Giulia Iannaccone; Raffaello Ditaranto; Federico Di Nicola; Serena Serratore; Antonella Lombardo; Letizia Spinelli; Guido Iaccarino; Elena Biagini; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Fabry disease can be classified in 4 stages based on the extent of cardiac damage assessed with echocardiography. This staging is strongly associated with prognosis, with a doubled risk increase of cardiovascular events for each stage progression. The aims of the present study were to investigate the evolution of cardiac damage using this staging system during midterm follow‐up and to identify predictors of stage worsening. Methods AND RESULTS This is a retrospective, multicenter study, which included 168 patients with Fabry disease (38% men) categorized at baseline and follow‐up in 4 stages, defined as follows: stage 0, no cardiac involvement; stage 1, left ventricular hypertrophy; stage 2, left atrial enlargement; and stage 3, ventricular impairment. After a median of 5 years, cardiac stage worsened of at least 1 class in 34 patients (24% of 143 patients in stage 0–2 at baseline), improved in 9 (12% of 73 patients in stages 1–3 at baseline), and remained stable in 125 (74% of the 168 patients enrolled). At multivariable logistic regression analysis, age (odds ratio, 1.05 [95% CI, 1.01–1.09]; P=0.006), male sex (odds ratio, 4.26 [95% CI, 1.54–11.79]; P=0.005), classic phenotype (odds ratio, 4.95 [95% CI, 1.30–18.72]; P=0.018), and renal failure (odds ratio, 10.40 [95% CI, 1.57–68.77]; P=0.015) emerged as independent predictors of cardiac damage stage deterioration. Conclusions Fabry disease is associated with a high rate of progression of cardiac damage during midterm follow‐up, with ≈24% of patients experiencing cardiac stage worsening. Age, male sex, classic phenotype, and renal failure are independent predictors of stage progression.